Investment analysis of Hungarian apple-orchard and fruit storage projects - Apáti, F.; Lakner, Z. (International Journal of Horticultural Science, 2016)
There are profound, long-term changes in world apple production and trade. The former hegemony of Europe in apple production doest not exists any more, among the most important apple exporters the emerging economies have a growing importance. The globalising apple market means new challenges of traditional producers. This is especially true for Hungary, which has been the most important apple exporter in terms of quantity thirty years ago, but now its production hardly covers the domestic demand. A necessary precondition of the modernisation is the re-construction of plantations and the cold-storage system. Analysing the economic effi ciency of apple production and cold storage, it is obvious, that a necessary precondition for the modern, competitive apple production is the availability of cold-storage facilities. Neither the apple-production, nor the cold-storage can not evaluated separately from each other. Under current Hungarian conditions there is a need for active state support for the establishment of cold-storage facilities.